Adventitious shoots from nodule cluster cultures of Vriesea reitzii: an endemic and endangered bromeliad from atlantic forest - Rech Filho,Arlindo (2009)
The Atlantic Forest is a biome with megadiversity and a number of bromeliads take part of it. This is the case of Vriesea reitzii, an endemic bromeliad threatened with extinction. Tissue culture techniques are valuable tools for the mass propagation of bromeliads, thus reducing pressure in the natural habitat. The aim of the present work was to establish an in vitro protocol based on the induction and proliferation of nodule cluster cultures of this species. Plantlets maintained in MS liquid culture medium plus NAA (2µM) and BAP (4µM) had the basal regions of leaves excised and then inoculated in gelled with agar (7g L-1) MS culture medium plus with Dicamba (2.5; 5; 10; 20 e 30µM) and Kin (2µM) or free of plant growth regulators. Nodule cluster cultures arose from the basal region of explants. The subculture to MS liquid medium plus GA3 (10µM) and in MS liquid medium free of plant growth regulators resulted in a high proliferation rate. The mean regenerative rate was 39 plantlets/0.03g of nodule culture. Plantlets were acclimatized in a mix substrate of 1:1 (v:v) of carbonized rice coat and Turfa Fertil® mineral supplement.